Methylparaben‐induced decrease in collagen production and viability of cultured human dermal fibroblasts. Issue 9 (6th April 2017) - Majewska, Natalia; Zaręba, Ilona; Surażyński, Arkadiusz; Galicka, Anna
Abstract: Parabens owing to their many advantageous properties are widely applied in cosmetics, food products and pharmaceuticals. However, recent research results have shown that they possess the ability to accumulate in the human body and exert many adverse effects. In this study, the impact of methylparaben (MP) as the most frequently used preservative in cosmetics, on human dermal fibroblasts and collagen production was evaluated. In cells treated with 0.01, 0.03 and 0.05% MP a dose‐dependent decrease in collagen biosynthesis was revealed, which was positively correlated with the activity of prolidase responsible for the recovery of proline. Consequently, the concentration of total collagen secreted into the medium was markedly diminished. A similar reduction in expression of the major skin collagen type I at both the protein and mRNA level as well as collagen type III and VI at the mRNA level was also detected. The decrease in the collagen level may result not only from the reduced synthesis but also increased degradation owing to MP‐induced activation of pro‐MMP‐2 (72 kDa). The increase in activity of MMP‐2 (66 kDa) was accompanied by a reduction in the inhibitory activity of TIMP‐2. In addition, an inhibitory effect of MP on cell survival and proliferation was revealed in this study. The increased expression and nuclear translocation of caspase‐3 as well as increased Bax and decreased Bcl‐2 expression may suggest MP‐induced cell apoptosis. In summary, we have provided new data on the adverse effects of methylparaben on human dermal fibroblasts and the main structural protein of the skin. Further studies on the mechanisms responsible for its action are in progress. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Parabens, despite their many adverse effects, are widely applied in cosmetics, food products and pharmaceuticals. This study provides new data on the inhibitory impact of methylparaben (MP) on collagen production as well as cell viability and proliferation of human dermal fibroblasts. Disturbances in collagen production may result from decreased collagen biosynthesis and increased degradation by MMP‐2. Changes in expression of caspase‐3, Bax and Bcl‐2 suggest MP‐induced cell apoptosis.